Direct and Indirect Spectrophotometric Determination of Paracetamol in Pharmaceutical Preparations By Oxidative Coupling With p-Amino-2-hydroxy Sodium Benzoate - Shakir, A. H.; Dikran, S.B.; Ali, K. F. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
New simple and sensitive spectrophotometric methods for the determination of paracetamol in aqueous medium were developed. The first method is based on coupling of paracetamol with p-amino-2-hydroxy sodium benzoate (AHB) in the presence of sodium periodate, as oxidizing agent, to form a brownish-orange compound which shows a Î»max at 470 nm. The molar absorptivity (Îµmax) of the colored product was found to be (3371) l.mole1.cm-1 and Sandelâ€™s index 0.0449 Î¼g.cm-2. The method follows Beerâ€™s law in the concentration range of 12.5-500.0 Î¼g of paracetamol in a final volume of 25 ml (0.5-20.0) Î¼g.ml-1 with relative standard deviation percent (R.S.D%) ranged between 0.26-4.71% and accuracy, expressed by recovery percent, 95-106% for five levels of parcetamol concentration.        The second method is based on indirect spectrophotometric procedure for the determination of paracetamol, after its hydrolysis in acidic medium and the reaction of hydrolyzed product (p-aminophenol) with p-amino-2-hydroxy sodium benzoate in the presence of sodium periodate in alkaline medium. A bluish-violet water soluble compound is formed with Î»max =580nm and Îµmax =11884 l.mole-1.cm-1 and Sandelâ€™s index 0.0127 Î¼g.cm-2. Beerâ€™s law is applicable for concentration range of paracetamol 12.5-500.0 Î¼g per 25 ml volume of solution (0.5-20.0) Î¼g.ml-1 with (R.S.D %) ranged between 0.60-1.10 % and recovery percent 94.28-101.6% for three levels of parcetamol concentration.  The proposed methods were successfully applied for the determination of paracetamol in pharmaceutical preparations by both direct and standard addition method and for three levels of concentration.